Quantifying Tidal Phase Effects on Coastal Flooding Induced by Hurricane Sandy in Manhattan, New York Using a Micro-Scale Hydrodynamic Model - Marsooli, Reza; Wang, Yifan (Frontiers in Built Environment, 2020)
This study investigates the effects of tidal phase on coastal flooding in New York City during Hurricane Sandy. A micro-scale hydrodynamic model is developed for Manhattan – the most densely populated borough of New York City – to accurately simulate coastal flooding in built environments. The model accounts for the effects of urban features on coastal flooding by resolving seawalls, buildings, and roads in the computational mesh. Model validation against high-water-mark measurements shows a root-mean-square-error of 15 cm and a bias of 7 cm. A series of numerical experiments are performed to investigate the effects of tide timing on the extent and depth of flooding in Manhattan. Model results show that the peak storm tide at The Battery tide gauge station, which is located immediately off of the southern tip of Manhattan, would have been 8.2% larger than the measured peak storm tide if Hurricane Sandy had arrived 12hr earlier. However, the extent of flooding would have been only 3% larger. If Sandy had arrived 6hr earlier, the peak storm tide would have been 27.2% smaller but the extent of coastal flooding in Manhattan would have been 69% larger. The model results indicate that the peak storm tide alone is not a good indicator for the extent of coastal flooding in urban areas. The floodwater velocity substantially impacts the extent of coastal flooding, suggesting that extra caution should be taken in using flood maps that are generated based on static modeling techniques, i.e. “bathtubbing”, that neglect the principles of fluid dynamics.